Effect of antibodies on the expression of Plasmodium falciparum circumsporozoite protein gene - Jesuíno, B. S. (2021)
Antibodies are known to play an important role in the control of malaria infection. However, they can modulate parasite development enhancing infection. The effect of anti-Plasmodium antibodies on the expression of circumsporozoite protein gene (csp) was investigated. Plasmodium falciparum 3D7 in vitro cultures were submitted to: i) anti- circumsporozoite protein monoclonal antibody (anti-CSP-mAb) [1μg/ml, 0.1μg/ml, 0.01μg/ml and 0.001μg/ml] and ii) purified IgG Fab fragment from a pool of malaria patients [1mg/ml and 1μg/ml]; and compared to control cultures. After 24h the number of ring infected erythrocytes was determined in order to calculate invasion efficacy. At 48h culture supernatant was collected, and the amount of circumsporozoite protein determined by ELISA, parasitaemia was calculated and cells were processed for RNA preparation. Expression of csp gene was quantified using Real time RT-PCR. There was an increase in parasite growth when treated with lower anti-CSP-mAb concentration, which was associated with lower csp expression, while 1μg/ml anti-CSP-mAb treatment presented a growth inhibitory effect accompanied by high csp expression.